Avaliação de proteínas recombinantes de leishmania no diagnóstico sorológico e como candidatas a compor uma vacina contra as leishmanioses - Vivian Tamietti Martins (2016)
The protection against reinfection by some Leishmania species indicates the possibility of development of a prophylactic vaccine against leishmaniasis. In the persuit for the selection of canditade antigens for composing a vaccine against VL and CL, in the present work, four Leishmania infantum proteins, named LiHyp1, LiHyp6, HRF and LiHyV, two CD8+ T cells epitopes extracted from LiHyV as well as a chimeric protein composed by immunodominant regions rich in CD4+ and CD8+ T cells epitopes present in these four proteins, were evaluated. The proteins were identified recently in amastigotes and/or promastigotes parasite forms and used in a recombinant form, individually, combined in a polypeptide vaccine or fused in a chimeric protein. The CD8+ T cell peptides selected from LiHyV protein were synthesized and administered separately as vaccine antigens. The immunogenicity of cadidates, associated with saponin, was tested in BALB/c mice and the vaccine efficacy was evaluated after the challenge with L. infantum or L. amazonensis promastigotes. The splenocytes of mice vaccinated with the recombinant proteins showed a high IFN-ɣ, IL-12 and GM-CSF production, together with a low production of IL-4 and IL-10, and when the animals were compared to control groups (saline and saponin), they showed a significant reduction in the parasite load in all the organs analysed. This protection was related to a high production of IFN-ɣ, which was mainly derived from T CD4+ cells. Also, the recombinant proteins (LiHyp1, LiHyp6, HRF e LiHyV) were assessed in their antigenicity for the serodiagnosis of canine visceral leishmaniasis (CVL). The proteins were recognized by antibodies present in sera from dogs with asymptomatic and symptomatic VL, and did not show cross-reactivity with antibodies present in dog sera with Chagas’ disease, ehrlichiosis, babesiosis or health dogs and/or vaccinated with the Leish-Tec® vaccine. This study showed new recombinant proteins that can be used for CVL serodiagnosis tests and, when associated with saponin, can compose an effective vaccine against visceral and tegumentar leishmaniasis.